Survey Of Anxiety And Self-Confidence Levels Of Badminton Athletes Before Competing In The Riau Kejurpov Championship: Anxiety and self-confidence or psychology - Aji, Shinta Kesuma; Endang Rini Sukamti; Tomoliyus Tomoliyus (CV. AFDIFAL MAJU BERKAH, 2025)
The study aims to determine the survey of anxiety levels and self-confidence of badminton athletes before competing in KEJURPROV Riau. This research method is a type of descriptive research. The population in this study were athletes who participated in the match with a research sample of 55 athletes. The analysis technique uses the formula: x 100%, find P (as the value of intrinsic, extrinsic, and confidence factors) find the percentage.The results of the study, the level of anxiety of badminton athletes before competing that the intrinsic factor is in the low category of 74.54%, because the intrinsic factor is a factor that exists within the athlete so that it can be trained during the training process. Indicators that influence the intrinsic factor are morale, competition experience, negative thoughts, and complacent thoughts. While the extrinsic factor is in the high category of 87.27%, because the extrinsic factor is a factor that exists outside the athlete so that anxiety can occur at any time beyond the athlete's expectations. Indicators that influence the extrinsic factor are coaches, spectators, opponents, referees, and facilities. While the results for the level of self-confidence of badminton athletes before competing are influenced by intrinsic factors with a percentage of 85.45%. For the results of the low extrinsic factor analysis with a percentage of 70.90%. This means that the level of self-confidence of badminton athletes before competing is influenced by intrinsic factors